A two-photon fluorescence, carbonized polymer dot (CPD)-based, wide range pH nanosensor: a view from the surface state. Issue 16 (14th April 2020) - Huo, Zepeng; Chen, Gang; Geng, Yijia; Cong, Lili; Pan, Lingyun; Xu, Weiqing; Xu, Shuping
Abstract : A low-toxicity, two-photon pH sensing carbonized polymer dot (CPD) was investigated from a view of surface state by means of the transient spectroscopy. Abstract : A green-emitting, low-toxicity carbonized polymer dot (CPD) with a high fluorescence quantum yield was synthesised by a simple hydrothermal method, and has been applied as a three-mode pH indicator and the pH readouts involve the intensity ratio of the absorption bands, the single-photon fluorescence, and the two-photon fluorescence (TPF) signals. The pH sensing mechanism of this CPD is dependent on the hydrogen ion regulation on its surface states, which is evidenced for the first time by transient spectroscopy. The rich surface states of this CPD allow a wider pH-responsive range relative to other carbon nanodot-based pH nanosensors. Its ultra-small size, low cell toxicity, high brightness and stability are conducive to intracellular pH sensing under the TPF imaging. Our study is helpful for the development of novel carbon-based sensing materials based on the design of the surface states. It also provides a new candidate for up-conversion photoluminescence-responsive imaging agents and it has potential applications in the diagnosis and dynamic monitoring of cells relying on the pH evolution.